Transepidermal UV radiation of scalp skin ex vivo induces hair follicle damage that is alleviated by the topical treatment with caffeine. (17th April 2019) - Gherardini, Jennifer; Wegner, Jeannine; Chéret, Jérémy; Ghatak, Sushmita; Lehmann, Janin; Alam, Majid; Jimenez, Francisco; Funk, Wolfgang; Böhm, Markus; Botchkareva, Natalia V.; Ward, Chris; Paus, Ralf; et al.
Abstract: Objectives: Although the effect of ultraviolet radiation (UVR) on human skin has been extensively studied, very little is known on how UVR impacts on hair follicle (HF) homeostasis. Here, we investigated how solar spectrum UVR that hits the human skin surface impacts on HF biology, and whether any detrimental effects can be mitigated by a widely used cosmetic and nutraceutical ingredient, caffeine. Methods: Human scalp skin with terminal HFs was irradiated transepidermally ex vivo using either 10 J/cm 2 UVA (340–440 nm) + 20 mJ/cm 2 UVB (290–320 nm) (low dose) or 50 J/cm 2 UVA + 50 mJ/cm 2 UVB (high dose) and organ‐cultured under serum‐free conditions for 1 or 3 days. 0.1% caffeine (5.15 mmol/L) was topically applied for 3 days prior to UV exposure with 40 J/cm 2 UVA + 40 mJ/cm 2 UVB and for 3 days after UVR. The effects on various toxicity and vitality read‐out parameters were measured in defined skin and HF compartments. Results: Consistent with previous results, transepidermal UVR exerted skin cytotoxicity and epidermal damage. Treatment with high and/or low UVA+UVB doses also induced oxidative DNA damage and cytotoxicity in human HFs. In addition, it decreased proliferation and promoted apoptosis of HF outer root sheath (ORS) and hair matrix (HM) keratinocytes, stimulated catagen development, differentially regulated the expression of HF growth factors, and induced perifollicular mast cell degranulation. UVR‐mediated HF damage was more severe after irradiation with high UVR dose and reached also proximal HF compartments. The topical application of 0.1% caffeine did not induce skin or HF cytotoxicity and stimulated the expression of IGF‐1 in the proximal HF ORS. However, it promoted keratinocyte apoptosis in selected HF compartments. Moreover, caffeine provided protection towards UVR‐mediated HF cytotoxicity and dystrophy, keratinocyte apoptosis, and tendential up‐regulation of the catagen‐promoting growth factor. Conclusion: Our study highlights the clinical relevance of our scalp UV irradiation ex vivo assay and provides the first evidence that transepidermal UV radiation negatively affects important human HF functions. This suggests that it is a sensible prophylactic strategy to integrate agents such as caffeine that can act as HF photoprotectants into sun‐protective cosmeceutical and nutraceutical formulations. Abstract : We show here that solar UVA+UVB radiation impacting on the skin surface negatively affects HF functions, namely it triggers HF cytotoxicity, dystrophy, oxidative DNA damage, decrease in keratinocyte proliferation and increase in their apoptosis, stimulation of the production of transforming growth factor (TGF)‐ β 2 and decrease in insulin growth factor (IGF)‐1 expression in ORS keratinocytes, premature catagen development, and perifollicular mast cell degranulation. UV‐mediated damage is present throughout the HF length, but is more prominent in the upper layers of the skin (distal HF), as compared to the lower HF (central and proximal). Our study also shows that the topical application of 0.1% caffeine protects HFs from UVR‐mediated damaged, namely it alleviated UV‐mediated HF cytotoxicity and dystrophy, keratinocyte apoptosis in the distal and central ORS, and increased expression of TGF‐ β 2 in the proximal ORS.